2009
DOI: 10.5012/bkcs.2009.30.1.077
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Activated Thrombin Activatable Fibrinolysis Inhibitor (TAFIa) and Inactivated TAFIa (TAFIai) in Normal and Hemophilia A Plasmas

Abstract: Thrombin activatable fibrinolysis inhibitor (TAFI) also known as plasma procarboxypeptidase B or U is a 60 kD glycoprotein, which is the major modulator of fibrinolysis in plasma. TAFI is a proenzyme, which is activated by proteolytic cleavage to an active carboxypeptidase B-like enzyme (TAFIa, 35.8 kD) by thrombin/thrombomodulin and plasmin. Modulation of fibrinolysis occurs when TAFIa enzymatically removes C-terminal lysine residues of partially degraded fibrin, thereby inhibiting the stimulation of tissue p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Further, Aso et al showed that low-density lipoprotein cholesterol was an independent determinant of plasma proCPU levels in 105 patients with type 2 diabetes mellitus (T2DM). In addition, subgroup analysis revealed significantly higher plasma proCPU levels in two subgroups: hypercholesterolemic diabetic patients with or without metabolic syndrome [102]. In another study, proCPU levels were reported to be significantly different in dyslipidemic and normolipidemic subjects, with higher values in the dyslipidemic group [137].…”
Section: Hyperlipidemiamentioning
confidence: 90%
See 1 more Smart Citation
“…Further, Aso et al showed that low-density lipoprotein cholesterol was an independent determinant of plasma proCPU levels in 105 patients with type 2 diabetes mellitus (T2DM). In addition, subgroup analysis revealed significantly higher plasma proCPU levels in two subgroups: hypercholesterolemic diabetic patients with or without metabolic syndrome [102]. In another study, proCPU levels were reported to be significantly different in dyslipidemic and normolipidemic subjects, with higher values in the dyslipidemic group [137].…”
Section: Hyperlipidemiamentioning
confidence: 90%
“…A second antibody pair measures the total amount of CPU + CPUi formed (MA-T30E5/MA-T17D7-HRP) [58,59,61,62,101]. Another assay that allows combined measurement of CPU and CPUi was published by Hulme et al [102]. This assay was marketed as the Imubind ® TAFIa/ai ELISA (US20060183172A1 and US7470519B2) but has been discontinued.…”
Section: Assessment Of Overall Procpu Activationmentioning
confidence: 99%